Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1093/pasj/psu101
|View full text |Cite
|
Sign up to set email alerts
|

Dwarf nova EZ Lyncis second visit to instability strip

Abstract: The analysis of 14 periodograms of EZ Lyn for the data spaced over 565 d in 2012-2014 (2-3.5 yr after 2010 outburst) yielded the existence of the stable signals around 100 c/d and three signals around 310 c/d, 338 c/d and 368 c/d (the corresponding periods are 864 s, 279 s, 256 s and 235 s). We interpret them as independent non-radial pulsations of the white dwarf in EZ Lyn, but a possibility that a linear combination of frequency at 100 c/d and harmonic of orbital period could produce the frequency at 368 c/d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 37 publications
2
6
0
Order By: Relevance
“…Still et al 2010). Although Kato and Uemura (2012) presented a code for single-epoch analysis, two-dimensional frequency analysis using Lasso has been employed and various results have been published (Kato and Maehara 2013;Osaki and Kato 2013;Kato and Osaki 2013a,b;Osaki and Kato 2014;Kato et al 2014b;Ohshima et al 2014;Kato et al 2014a;Pavlenko et al 2014;Kato et al 2015b;Kato et al 2015a;Kato et al 2016;Niijima et al 2021). In Osaki andKato (2013, 2014), Lasso analysis played an important role in demonstrating the conclusion that the thermal-tidal instability model (Osaki 1989) is the only viable model to explain superoutbursts in SU UMa stars.…”
Section: Introductionmentioning
confidence: 99%
“…Still et al 2010). Although Kato and Uemura (2012) presented a code for single-epoch analysis, two-dimensional frequency analysis using Lasso has been employed and various results have been published (Kato and Maehara 2013;Osaki and Kato 2013;Kato and Osaki 2013a,b;Osaki and Kato 2014;Kato et al 2014b;Ohshima et al 2014;Kato et al 2014a;Pavlenko et al 2014;Kato et al 2015b;Kato et al 2015a;Kato et al 2016;Niijima et al 2021). In Osaki andKato (2013, 2014), Lasso analysis played an important role in demonstrating the conclusion that the thermal-tidal instability model (Osaki 1989) is the only viable model to explain superoutbursts in SU UMa stars.…”
Section: Introductionmentioning
confidence: 99%
“…These periods include a known "period gap" between 2 and 3 hours for the cataclysmic variables distribution. However, as it was shown on the basis of a large number of examples (Pavlenko et al 2014;Kato et al 2017a), SU UMa stars in the period gap display rather extension of monotonic decrease of the stars number toward the long-periodic border of the gap instead of an abrupt shortage of them.…”
Section: Introductionmentioning
confidence: 84%
“…Sheets et al (2007) used radial velocities to find the orbital period of 0 d .09903(9). The second time V1006 Cyg was found in rather wide outbursts lasting more than six days in 2007 and more than five days in 2009 (Pavlenko et al 2014), but no superhumps were observed. Instead the orbital period was detected in both outbursts by Pavlenko et al (2014).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…About 7 months after the 2010 outburstPavlenko et al (2012) found a much shorter periodicity at 4.28 min (3.89 mHz) Szkody et al (2013a). confirmed it 14 months after the 2010 outburst by UV observations with HST (Hubble Space Telescope) as well as ground-based optical obser-vations (Pavlenko et al (2014). reported a higher frequency at 4.25 mHz present for a week in 2012 November.)…”
mentioning
confidence: 87%